Faktor-Faktor Yang Mempengaruhi Ibu Terhadap Status Imunisasi Dasar Pada Bayi Usia 12-24 Bulan di Desa Nauli Kec. Sigumpar Kab.Toba Tahun 2023 - Jane Wilda Irmawati Sirait (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Immunization is an act of providing immunity to children against diseases that can be prevented by immunization before the age of 12 months, namely tuberculosis, polio, hepatitis B, diphtheria, pertussis, tetanus and measles. Complete and regular basic immunization by receiving all types of basic immunization when children are less than 11 months old can reduce morbidity and mortality rates for toddlers by around 80-95%. Incomplete basic immunization, maximum can only provide 25-40% protection. The role of a mother in the immunization program is very important, because the use of health facilities by babies/children is related to factors that influence the mother. The aim of this study was to determine the relationship between factors that influence mothers on basic immunization status in babies aged 12-24 months. This research uses a descriptive correlation design with a cross sectional approach. The number of samples in this study was 40 people. Sampling was taken using the total population. This research was conducted in Nauli Village, Sigumpar District, Toba Regency in 2023. The instrument in this research was a questionnaire. Data analysis used chi-square. From the research results, it was concluded that there was a significant relationship between maternal age with a value of p=0.001, education with a value of p=0.004, employment with a value of p=0.001, number of children with a value of p=0.000, and knowledge with a value of p=0.000 on basic immunization status . From this research, it is hoped that health workers will improve the quality of health services, health promotion efforts in the form of social support, namely improving the quality of health education, providing motivation in utilizing health services, especially immunization.